Synthesis, Characterization and Anticrobial Studies of Some Bivalent Metal Complexes with 1-Phenoloxy-2-(3’-methyl-5’-mercapto-1’,2’,4’-triazole)-2-azaethane - Jha, R.R.; Mukherjee, P. (Asian Journal of Chemistry, 2010)
Metal complexes of the type [M(PMTE)(H2O)2] [where M = Mn(II), Co(II) or Ni(II) and PMTE=1-phenoloxy-2-(3prime-methyl-5prime-mercapto-1prime,2prime,4prime-triazole)-2-azaethane] and [Cu(PMTE)]2 have been synthesized in neutral medium. The IR spectra of the complexes suggest the coordination of the metal ion and ligand through thiol-sulphur, exocyclic azomethine nitrogen and phenolic oxygen. Octahedral geometry of the complexes except [Cu(PMTE)]2 have been proposed on the basis of elemental analysis, magnetic susceptibility measurement and spectra studies. However, for the Cu(II) complex squareplanar geometry has been proposed. Thermal analyses of all the complexes except [Cu(PMTE)]2 show silar pattern of decomposition. Weight loss around ca. 210ºC in one step with exothermal peak in DTA curve corresponds to loss of two water molecules, characteristic of coordinated water molecule. Decomposition of all the complexes starts at ca. 355ºC and ternates at ca. 780ºC with a final residue corresponding to the formation of metal oxide. Fungicidal screening of the complexes show them active against Aspergillus niger, Fusarium orysporium and Helnthosporium oryzae.